The role of AI and ML in transforming last mile delivery - Xoxi, Ejona (2025)
This paper aims to explore the prospective of Artificial Intelligence (AI) and Machine Learning (ML) adaptation in LMD. AI technologies are used in LMD to address the current issues that the industry is facing and to improve efficiency. This research aims to investigate the current AI technologies that are prevailing in adaptation, the user experience, and the benefits gained from their use. The study uses a mixed-methods approach that includes a mix of qualitative research through semi-structured interviews and quantitative research through a survey. The research has been conducted among the Philippines and the Czech Republic professionals’ working in LMD. The results of interviews and the survey for each country were analyzed and used to compare points of similarity and difference. In order to understand best practices and gaps that provide additional value to this thesis research.